Model comparison in simulating the atmospheric dispersion of a pollutant plume in low wind conditions. (13th October 2012) - Ghermandi, Grazia; Teggi, Sergio; Fabbi, Sara; Bigi, Alessandro; Cecchi, Rodolfo
This study investigates the performance of different air pollution dispersion models in low wind conditions. The models have been applied to two sites frequently characterised by weak winds: the cities of Modena and Reggio Emilia, in the Po River Valley (Northern Italy). The emission sources are the municipal waste incinerator (Modena) and a turbogas plant (Reggio Emilia). Total Suspended Particulate (TSP) concentration levels are estimated by the gaussian Industrial Source Complex (ISC3) and WinDimula 3.0 models, and the Langrangian model SPRAY. WinDimula 3.0 and SPRAY simulations perform significantly better than ISC3, SPRAY shows the highest reliability close to the source.